The four conversations : daily communication that gets results - Ford, Jeffrey (Berrett-Koehler Publishers, 2009)
Annotation This book shows managers and employees how to use the right conversation at the right time, plan and start each conversation well, and finish each conversation effectively.
Keywords: Communication in management.; Interpersonal communication.; Business communication.; elektronické knihy; electronic books